2002
DOI: 10.1128/aac.46.9.2943-2947.2002
|View full text |Cite
|
Sign up to set email alerts
|

Application of Real-Time PCR for Determination of Antiviral Drug Susceptibility of Herpes Simplex Virus

Abstract: A quantitative real-time PCR (TaqMan) assay was developed for determination of antiviral drug susceptibility of herpes simplex virus (HSV). After short-time culture of the virus, the antiviral drug susceptibility of HSV isolates for acyclovir (ACV) was determined by measuring the reduction of the HSV type 1 (HSV-1) DNA levels in culture supernatants using real-time PCR. The 50% inhibitory concentration was reported as the concentration of antiviral drug that reduced the number of HSV-1 DNA copies by 50%. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Because the highest concentration of Myt-Tat used in these assays did not allow calculation of the CC 50 value, it can only be suggested that the CC 50 would be higher than 32.6 M. Therefore, the putative SI values for Myt-Tat would be Ͼ8.21 against HSV-1 and Ͼ10.5 against HSV-2. The EC 50 s obtained for ACV, which was used as a positive control in the antiviral activity assay (EC 50 s, 0.9 g/ml for HSV-1 and 1.1 g/ml for HSV-2), are in agreement with previous studies (32,33) and suggested that both the HSV-1 and HSV-2 isolates used throughout this study are sensitive to acyclovir (EC 50 Ͻ 2 g/ml) (34).…”
Section: Figsupporting
confidence: 77%
“…Because the highest concentration of Myt-Tat used in these assays did not allow calculation of the CC 50 value, it can only be suggested that the CC 50 would be higher than 32.6 M. Therefore, the putative SI values for Myt-Tat would be Ͼ8.21 against HSV-1 and Ͼ10.5 against HSV-2. The EC 50 s obtained for ACV, which was used as a positive control in the antiviral activity assay (EC 50 s, 0.9 g/ml for HSV-1 and 1.1 g/ml for HSV-2), are in agreement with previous studies (32,33) and suggested that both the HSV-1 and HSV-2 isolates used throughout this study are sensitive to acyclovir (EC 50 Ͻ 2 g/ml) (34).…”
Section: Figsupporting
confidence: 77%
“…According to preliminary data, the overall efficiency of PCR assay was not modified when either a 10-foldhigher MOI or primary HHV-6 isolates growing on peripheral blood mononuclear cells were used (not shown). This reflected its robustness and adaptability, confirming similar recent results obtained with a herpes simplex virus real-time PCR assay (13).…”
supporting
confidence: 78%
“…The ACV EC 50 values obtained were 2.8 mg/ml for HSV-1 strain 8ACV, previously described as ACV-resistant; 1.2 mg/ml for the ACV-sensitive HSV-1 strain 2677, and 5.1 mg/ml for the ACV-resistant HSV-2 clinical isolate 2373. It should be mentioned that an EC 50 value of 2 mg/ml or greater, is considered as indicative of ACV resistance of a HSV strain, as has been previously reported (Stranska et al 2002).…”
Section: Article In Pressmentioning
confidence: 99%